Governmental Performance in Integrated Stunting Countermeasures in Border Regions: Evidence from Timur Tengah Utara Regency - Tri Anggraini; Handrianus Vianey Melin Wula (FISIP Universitas Islam Negeri Raden Fatah Palembang, 2021)
Handling stunting in North Central Timor Regency (TTU) by involving many sectors is greatly influenced by the functions of supervision and control, to carry out supervision and control the bureaucracy requires hierarchy. hierarchy used in bureaucracy cannot be done haphazardly, there needs to be careful efforts because hierarchical bureaucracy has a dual role can be a strength as well as weakness of bureaucracy. The research will focus on analyzing the application of hierarchical bureaucracy in efforts to tackle integrated stunting in border areas. The study uses descriptive methods with qualitative approaches with the use of observation methods and in-depth interviews. The results showed that, in efforts to handle stunting, the TTU Regency government uses a type of Long Hierarchy on the grounds of a broad range of stunting policy areas, with the benefit of providing limits on authority, facilitating communication and coordination, clarifying communication channels and accountability and assisting leaders in efforts to control stunting countermeasures policies. But on the other hand, the use of long hierarchies has an impact on the optimal performance of bureaucracy indicated by negative impacts, among others, the old decision-making process, causing subordinate dependence on superiors in decision-making efforts and coordination and supervision systems between related sectors, takes longer and can almost cooperation between sectors. Therefore, efforts are needed to develop information and communication technology (ICT) to replace some of the functions of the hierarchy and become a fast communication medium for leaders in conducting supervision and control activities. The use of ICT can be used by all actors in the bureaucracy, both superiors and subordinates to control each other's stunting activities in Timur Tengah Utara Regency.